2008
DOI: 10.1152/ajpregu.00166.2008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brain mRNA levels of gonadotropin-releasing hormone, pituitary adenylate cyclase activating polypeptide, and somatostatin during ovulatory luteinizing hormone and growth hormone surges in goldfish

Abstract: Canosa LF, Stacey N, Peter RE. Changes in brain mRNA levels of gonadotropin-releasing hormone, pituitary adenylate cyclase activating polypeptide, and somatostatin during ovulatory luteinizing hormone and growth hormone surges in goldfish. Am J Physiol Regul Integr Comp Physiol 295: R1815-R1821, 2008. First published September 24, 2008 doi:10.1152/ajpregu.00166.2008.-In goldfish, circulating LH and growth hormone (GH) levels surge at the time of ovulation. In the present study, changes in gene expression of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…Additionally, such increases in GH cell activity in the vitellogenic stage could be related to increased feeding during this period, as was observed in other teleost fish (Holloway and Leatherland 1998). It is also probable that in this species, GH secretion is regulated by melatonin, as observed in rainbow trout ( Oncorhynchus mykiss ), and/or by GnRH as suggested by Canosa et al (2008), who demonstrated that the circulating levels of LH and GH increase at the time of ovulation in goldfish.…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, such increases in GH cell activity in the vitellogenic stage could be related to increased feeding during this period, as was observed in other teleost fish (Holloway and Leatherland 1998). It is also probable that in this species, GH secretion is regulated by melatonin, as observed in rainbow trout ( Oncorhynchus mykiss ), and/or by GnRH as suggested by Canosa et al (2008), who demonstrated that the circulating levels of LH and GH increase at the time of ovulation in goldfish.…”
Section: Discussionmentioning
confidence: 75%
“…However, the influence of circulating SST on the control of GH secretion has not been clearly addressed in fish. The regulation of GH by SST may be influenced by developmental stage, feeding, and nutritional state [84,85]. Other research suggests that SSTs are involved in the regulation of growth hormone sensitivity of fish hepatocytes, and can cause a reduction in the levels of GHR expression and IGF-1 biosynthesis and secretion [86,87].…”
Section: Growth Hormone Inhibiting Hormone (Ghih or Somatostatin Sst)mentioning
confidence: 99%
“…In the goldfish, GnRH2 stimulates reproductive behavior (188). Furthermore, there is a strong positive correlation between spawning behavior and GnRH2 gene expression (189), suggesting stimulatory role of GnRH2 in reproductive behavior. GnRH2 is also detected in the goldfish pituitary (190) and induces LH release in vitro (120).…”
Section: Metabolic Neuropeptides Involved In Reproductionmentioning
confidence: 99%